Experimental research on seismic retrofitting of R/C corner beam-column-slab joints upgraded with carbon fiber reinforced polymer (CFRP) sheets - Topcu, İbrahim. (Thesis (M.S.)-Bogazici University. Institute for Graduate Studies in Science and Engineering, 2008., 2008)
An experimental study was conducted on seismically deficient RC corner connections with and without floor slab in order to examine the behavior under seismic action and to develop proper strengthening techniques. Four 2/3 scale specimens were tested which were designed according to pre 1970’s USA design codes. The specimens were designed to simulate non-ductile detailing characteristics of pre-seismic codes construction. Therefore, they contained some typical detailing deficiencies; 1) lapped splices of column reinforcement just above the joint region, 2) widely spaced column ties, 3) no transverse reinforcement within the beam-column joint, and 4) discontinuous positive beam reinforcement with a short embedment length into the column. Carbon fiber reinforced polymers (CFRP), which were placed around potential hinging zones, were used to strengthen the specimens with floor slab in order to overcome these deficiencies. The specimens were tested under constant axial load, with a magnitude of 700 kN (30% of axial load capacity of the column), and reversed cyclic lateral load. The test results showed that RC corner connections with above mentioned deficiencies were subjected to the brittle joint shear and bond-slip failures under seismic action. The tested strengthening techniques were successful in delaying and limiting the joint shear and bond-slip failures. CFRP application also improved lateral load versus drift response, energy dissipation potential and stiffness degradation characteristics of deficient subassemblies.
Keywords: Fiber-reinforced plastics.; Joints (Engineering)